IMPLEMENTASI PERATURAN MENTERI KOPERASI NOMOR 6 TAHUN 2020 TERHADAP PENINGKATAN PEREKONOMIAN PELAKU UMKM DI DESA MON PASONG KECAMATAN WOYLA BARAT KABUPATEN ACEH BARAT - Erick, Benni; Novia, Santi (CONSTITUO : Jurnal Riset Hukum Kenegaraan dan Politik, 2023)
ABSTRACT The implementation of the Ministry of Cooperative and SMEs Regulation No. 6 of 2020 is one of the government’s efforts to help MSMEs during the Covid-19 period. Because of this assistance, at least it can alleviate the economic problem Mon Pasong People in meeting their daily economic needs, business capital provided by the government is very helpful to businesses run by the community or business that is being occupied, this effort is carried out in an effort to develop and increase self-sefficiency economy gradually. The objectives to be achieved from this research are : (1) to find out the mechanism for obtaining BPUM assistance provided from Ministry of Cooperative and SME’s Regulation No 6 of 2020 Implementation, (2) to find out the efforts made by MSMEs to improving the economic in Mon Pasong Village, (3) to find out the obstacles faced by MSME who receive BPUM assistance in improving the economic in Mon Pasong Village. This study used qualitative methods with data collection techniques, interview and documentation. In analyzing the data using descriptive qualitative analysis method. From this research it can be described that : (1) The implementation of Ministry of Cooperative and SMEs Regulation No 6 of 2020 for MSMEs has provided an opportunity for MSMEs in Mon Pasong Village, West Woyla District to receive BPUM resistanse. Communities in Mon Pasong have received BPUM asistance starting from 2020 to 2022, (2) effort made by Mon Pasong community to obtain assistance for business by submitting an application to Perindagkop by completing the requirements for photocopy of KTP, KK, business certificate and opening a bank account. This assistance is very helpfull for community to increase their business and feel the impact on improving the local community’s economiy, (3) The constraints faced by micro-entrepreneurs in Woyla are difficulty of getting access and fast information, due to the unvailability of a good internet network, considering that the West Woyla is a remote rural area. Keywords : Implementation, Ministry of Cooperative and SMEs No 6 of 2020 Regulation, Economy, MSME.